Mystery Shopping and Well-Being of Service Workers in South Korea - Heeju Shin (Elsevier, 2019)
Background: Mystery shopping is a method in which a company monitors quality of service and employee conduct and compliance with regulations using an evaluator posing as a customer. It is a typical tool of customer-centered bureaucratic control insofar as it provides overall and standardized evaluation of intangible elements of customer service as well as physical elements of service environments. The purpose of this study is to examine how mystery shopping is related to the health status of service workers in South Korea. Methods: Data from semistructured interviews with 15 workers were collected from January to April 2019 to obtain information on service worker experiences with mystery shopping. Data were analyzed using the constant comparison method. Results: Mystery shopping limits worker autonomy and stiffens the workplace environment by standardizing and monitoring labor processes for service workers. In addition, mystery shopping heightens work stress through increased labor intensity. Five mechanisms by which mystery shopping affects service worker health are identified and comprise (1) multifaceted and multilayered surveillance, (2) evaluator subjectivity and irrational requirements, (3) standardized rules combined with high pressure to achieve sales, (4) self-esteem degradation because of evaluator results, and (5) musculoskeletal disorders because of strict adherence to labor processes based on evaluator results. Conclusion: Mystery shopping as an evaluation method should be reconsidered not only in terms of health problems but also in terms of organizational efficiency and issues of human rights. Keywords: Bureaucratic control, Job autonomy, Job stress, Mystery shopping, Surveillance